A honeybee social foraging algorithm for feedback control of smart lights. (February 2016) - Alfonso, Wilfredo; Velásquez, José J.; Passino, Kevin M.; Caicedo, Eduardo F.
Abstract: In contrast to the wide array of research that uses swarm intelligence to solve optimization problems, a few approaches have recently been taken a feedback control perspective as we do here. To employ a feedback control approach, this paper shows that an algorithmic model of how honeybees forage can be used for control of smart lights. We show that only slight modifications to this model are needed to control multiple lights and to provide uniform illumination across the floor of an experimental testbed. The most challenging case is when there are no walls between lighting zones since then there are a significant inter-zone couplings, and the approach here performs especially well under these conditions. Performance of this method is compared with a variety of testbed conditions where we assume inter-zone coupling as overlapping sources. Experimental results supported by parametric statistical tests suggest that the method here is better when significant overlapping is addressed.